PENGARUH PENGGUNAAN PUPUK KOMPOS DARI SERBUK KAYU TERHADAP PERTUMBUHAN TANAMAN JAGUNG - Sembiring, Ika Septina; Gea, Karunia; Manao, Leonardus Historis; Waruwu, Hasalinus (Universitas Nias Raya, 2024)
This research aims to determine the effect of using compost from wood dust on the growth of corn plants (Zea Mays L). This type of research is quantitative research with pure experimental methods (true experiments). The population of this study was corn plants (Zea Mays L.) in 30 polybags. This research sample used simple random sampling consisting of 30 polybags of corn plants (Zea Mays L.) with six treatments and five replications. The treatments applied were P0 (without fertilizer), P1 (5 kg), P2 (4 kg), P3 (3 kg), P4 (2 kg), P5 (1kg). This research data was analyzed using the SPSS application version 20. Based on the analysis using the one way anova test, it showed that the application of wood compost powder to the P5 treatment (5 kg) on ​​corn plants had a very real influence on stem height, number of leaves and stem diameter of corn plants. . . The results of data analysis from the Tukey HSD Least Significant Difference (BNT) test also show that the Fcount > Ftable value means Ho is rejected and Ha is accepted. This is because the more compost dose given, the more N contained in the bokashi will be received by the soil. Based on the research results, it shows that the use of sawdust compost has a real influence on the growth of corn plants (Zea Mays L.). The advice offered by researchers is that the use of compost should be increased to overcome the scarcity and high cost of inorganic fertilizers.